2013
DOI: 10.1016/j.lungcan.2013.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Smoking status and self-reported race affect the frequency of clinically relevant oncogenic alterations in non-small-cell lung cancers at a United States-based academic medical practice

Abstract: Introduction The identification of somatic genomic aberrations in non-small-cell lung cancer (NSCLC) is part of evidence-based practice guidelines for care of patients with NSCLC. We sought to establish the frequency and correlates of these changes in routine patient-tumor sample pairs. Methods Clinicopathologic data and tumor genotype were retrospectively compiled and analyzed from an overall cohort of 381 patient-tumor samples. Results Of these patients, 75.9% self-reported White race, 13.1% Asian, 6.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
58
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 33 publications
4
58
1
Order By: Relevance
“…Previous studies found similar overall distributions of ALK rearrangements between NSCLC patients of Asian and Caucasian descent [43], [76]. However in this meta-analysis, the prevalence of ALK rearrangements was heterogeneous between East Asians and Caucasians in terms of age, gender and histology.…”
Section: Discussionmentioning
confidence: 43%
“…Previous studies found similar overall distributions of ALK rearrangements between NSCLC patients of Asian and Caucasian descent [43], [76]. However in this meta-analysis, the prevalence of ALK rearrangements was heterogeneous between East Asians and Caucasians in terms of age, gender and histology.…”
Section: Discussionmentioning
confidence: 43%
“…Lung cancer patients with identified driver genomic alterations treated with a targeted therapy survive longer than those who did not receive a targeted therapy (2). KRAS mutations are the most prevalent oncogenic driver mutation, detected in 30% of smokers and 10% of never-smokers with lung adenocarcinoma in Western populations (3)(4)(5). In contrast, for patients with KRAS mutations, targeted therapies have been largely unsuccessful and chemotherapy remains the current standard of care.…”
Section: Introductionmentioning
confidence: 99%
“…The p53 mutation is significantly more frequent in lung carcinomas of smokers than in those of nonsmokers [18], and some papers have described widely dispersed p53 point mutations in the precancerous dysplastic bronchial epithelium of smokers [19,20]. On the other hand, EGFR mutations and ALK rearrangements are less common in smoking-related than in non-smoking-related lung cancer [21,22]. These reports and the results of the present study suggest that the mechanism of lung carcinogenesis in smokers differs from that in nonsmokers.…”
Section: Discussionmentioning
confidence: 99%